Concentration of Primary, Secondary, and Micronutrient Elements in Different Parts of ‘Hom Thong’ Banana (Musa AAA Group) - Prommase, Pornprom; Muangtip, Kesorn; Chaowiset, Wirot; Thaikert, Ratchadaporn (YRU Journal of Science and Technology, 2026)
Hom Thong banana is a significant economic crop in Thailand. However, there is limited information regarding nutrient accumulation patterns within its various plant parts, which is essential for effective fertilizer management and the efficient utilization of plant residues. Therefore, this study aimed to investigate the nutrient accumulation in different parts of Hom Thong banana at the 9-month harvest stages from a plantation in Saitong Subdistrict, Chaiburi District, Surat Thani Province. A total of 30 harvest-ready plants were randomly selected from three rows, and the experiment was arranged in a randomized complete block design (RCBD) with four treatments: (1) pseudo stem, (2) leaf, (3) fruit, and (4) banana blossom. The results showed that nutrient accumulation varied significantly among plant parts (p < 0.05). In the pseudo stem, macronutrient concentrations were highest for K (4.33%), while the micronutrients were dominated by Mn (492.21 mg/kg). In the leaves, K was also highest (2.71%) with Mn (1,107.78 mg/kg) being the most abundant micronutrient. In the fruit, K was highest (2.28%) among micronutrients, Fe was highest (105.51 mg/kg). In the banana blossom, K was highest (5.77%), while Mn (396.23 mg/kg) was the dominant micronutrient.